Distribution pattern of weed seedbank in strip and bed planted sandy clay loam soil after five years of cropping in Bangladesh: Effect of strip and bed planting on soil weed seedbank - Hossain, Mobarak; Begum, M; Rahman, M M (Journal of Current Opinion in Crop Science, 2021)
Tillage practices can alter the distribution of weed seedbank and might be a useful tool for integrated weed management. The objective of this shade house experiment was to study the effects of strip planting (SP) and bed planting (BP) relative to conventional tillage (CT) with increased residue mulching (20 vs. 50%) of previous crops on the floristic composition of weeds in the field. A five-years longer conservation agriculture experiment was sampled from the Rajshahi district of Bangladesh. The weed seedbank in 0-15 cm soil was quantified by assessing weeds emergence during January-December 2016. The year-round count of emerged weeds revealed the fewest number of weed species (especially broadleaf weeds) and lowest weed density in SP, followed by CT and BP with 50% mulches. The SP and BP produced a higher number of perennials weeds than annual weeds, which was the opposite of CT. Therefore, it could be concluded that continuous practice of SP and increased crop residue retention for five years decreased the weed seedbank size. Still, they increased the relative proliferation of perennial weeds compared to CT. Weed seedbank size in SP was even smaller than BP.